Prevalence of nutrient canals in diabetes mellitus and hypertension: A radiographic study - Sudhaa Mani; Harsha Vardhan; Ravindranath; James Manohar; Jayakrishna; Maheswar (Wolters Kluwer Medknow Publications, 2013)
Aim: The present study is undertaken primarily to determine if a correlation in the appearance of nutrient canals with hypertension and diabetes exists and to determine whether the presence of nutrient canals can be used as a clue for the detection of hypertensive and diabetic patients. Patients and Methods: A total of 300 subjects were selected from the out-patient department comprising of 100 diabetic patients, 100 hypertensive patients and 100 patients without any systemic diseases as control group. Intraoral periapical radiograph of all these patients were taken for evaluation. Statistical Analysis Used: Statistical analysis of the data was done using the statistical package for the social sciences (SPSS 15.0) using Chi-square analysis. Differences were considered as significant when P ≤ 0.05. Results: Of all these 300 patients, 162 patients exhibited nutrient canals whereas 118 patients didn't have nutrient canals. Of the 100 patients in Group I, 62 patients exhibited nutrient canals which accounts to 62% prevalence, 64 out of 100 patients in Group II, exhibited nutrient canals which account to 64% prevalence and 72 out of 100 patients in control group exhibited nutrient canals which account to 36% prevalence. Conclusion: As the study showed positive correlation, we conclude same that presence of nutrient canal can be used as an aid to rule out systemic diseases like diebeeis mellitus and hypertension.